(3TQM ThGgO GdeaUds - (3eXgQ GdOjf eMeOs; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd GdEfSGf hHYO abO efM Cf CcJH Ydi eG MHi Hg GdMHQ GdYdGeI LGQ Gddg GdReNTQi cJGHI GdeaUd GYde EYdGekG ef GdCaYGd GdeJYOjI s
(3BNQgG (B:s
(3hbhdg jVef UaI GdHjJ hGdWGFe eaYhd KGf dJVefg hjMhjgG CeG UaI ddWGFe ChMGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3hQO ai cTa GdXfhf L(B2 (3U` (B1774 (3Cf GdeaUd dLGQ Gddg GdReNTQis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdeLGejYs